Religious awareness as a cognitive anchor for moral resilience: Evidence from vocational school students in Indonesia - Zamzam Badrouzzaman; Yoga Tri Cahyono; Umi Muthiyah Wardatul Janah; Rodhia Dyah Hesti; Surawan Surawan (Universitas Ahmad Dahlan, 2026)
Moral resilience is a critical aspect of adolescent development, particularly within vocational education contexts characterized by substantial social and professional pressures. However, the psychological mechanisms explaining the role of religious awareness in fostering moral resilience remain underexplored. This study aimed to examine the relationship between religious awareness and moral resilience among vocational high school students. This study employed a quantitative cross-sectional correlational design as a preliminary investigation. A total of 26 students (M age = 16.50, SD = 0.85) from a single class at Al-Ishlah Vocational High School, Palangka Raya, Indonesia, participated using a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using Pearson correlation and simple linear regression. The findings revealed a significant positive relationship between religious awareness and moral resilience (r = .769, p < .001). Regression analysis indicated that religious awareness significantly predicted moral resilience (R² = .592, p < .001). Religious awareness plays an important psychological role in shaping students’ moral resilience. The findings support the perspective that the internalization of religious values contributes to moral regulation within vocational adolescent contexts.